2018
DOI: 10.3390/app8112024
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Property of Sn-58Bi Solder Paste Strengthened by Resin

Abstract: Sn-58Bi solder has been widely used for microelectronics packaging due to its low melting point temperature, good wetting performance, good mechanical properties, and low cost. Compared with Sn-Bi solder alloy and Sn-Pb solder alloy, the strength and plasticity of Sn-Bi solder are not enough, due to the higher brittleness of bismuth, which thus limits the application of Sn-Bi solder. In order to improve the properties of Sn-Bi solder, a novel solder paste strengthened with resin was developed by mixing epoxy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…The Sn-Bi composite solder paste with thermosetting epoxy with different proportions (3 wt.%, 5 wt.%, and 7 wt.%) (TSEP Sn-Bi-x, x = 3, 5, 7) was used to print on the PCB side, forming the hybrid Sn-Bi/TSEP Sn-Bi-3, Sn-Bi/TSEP Sn-Bi-5, and Sn-Bi/TSEP Sn-Bi-y solder joints. The TSEP Sn-Bi solder paste was prepared using Sn-Bi solder powder (particle size 25-45μm), flux, and epoxy system, and the epoxy resin system consisted of thermosetting epoxy resin and a curing agent, which can be seen in previous studies regarding the preparation of TSEP Sn-Bi solder paste [20,22]. Figure 2 illustrates a two-part schematic diagram of the drop test specimen's preparation process.…”
Section: Preparation Of Test Specimenmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sn-Bi composite solder paste with thermosetting epoxy with different proportions (3 wt.%, 5 wt.%, and 7 wt.%) (TSEP Sn-Bi-x, x = 3, 5, 7) was used to print on the PCB side, forming the hybrid Sn-Bi/TSEP Sn-Bi-3, Sn-Bi/TSEP Sn-Bi-5, and Sn-Bi/TSEP Sn-Bi-y solder joints. The TSEP Sn-Bi solder paste was prepared using Sn-Bi solder powder (particle size 25-45μm), flux, and epoxy system, and the epoxy resin system consisted of thermosetting epoxy resin and a curing agent, which can be seen in previous studies regarding the preparation of TSEP Sn-Bi solder paste [20,22]. Figure 2 illustrates a two-part schematic diagram of the drop test specimen's preparation process.…”
Section: Preparation Of Test Specimenmentioning
confidence: 99%
“…Although many studies demonstrated that the addition of the third element or nanoparticles to Sn-Bi eutectic alloy benefitted the properties of solder joints, the complexity of the material's preparation process and the problem of cost increase were needed to be considered. To overcome these issues, the Sn-Bi composite solder paste with thermosetting epoxy (TSEP Sn-Bi) was mentioned to prepare the high-performance joint in our previous studies [20,21]. After the thermal cycling test and temperature and humidity test, the TSEP Sn-Bi solder joints demonstrated better mechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…After the formation of the solder joint, the epoxy-based resin is cured, providing reliable physical, chemical, and electrical protection. The enhancement effect of the ESP on the lifetime of solder joints has been clearly recognized by thermomechanical reliability analysis [ 14 , 15 ]. Fukumoto et al introduced thermoplastic polyester resins into ESPs consisting of epoxy-based thermoset resins, curing agents, and diethyl glutaric acid as the reducing agent for self-organization soldering [ 16 ] and prevention of spreading of the ESP [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common solder alloys, such as Sn-Ag and Sn-Cu solder alloys have melting point temperatures higher than 200 • C (221 and 227 • C, respectively) while for low-temperature soldering conditions, only Sn-Bi and Sn-In systems may be used, whose melting points are below 180 • C (138-170 and 118-145 • C, respectively) [2,8,9].…”
Section: Introductionmentioning
confidence: 99%